DESAIN APLIKASI INTERAKTIF MODEL PEMBELAJARAN AKUNTANSI BAGI SISWA SEKOLAH MENENGAH KEJURUAN - Chitra Santi; Melvie Paramitha; Minny Elisa Yanggah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2019)
The rapid development of technology, will have an impact on learning methods in schools. The learning method will begin to shift from manual methods to learning methods using applications / software. Schools are required to be able to create appropriate learning methods and produce graduates who are proficient in operating technology such as making financial reports using software as a means of accounting knowledge. The purpose of this study is to design a technology-based accounting learning model to facilitate and motivate accounting learning for vocational students. The approach of this research is an explorative research of a technical applicative nature with a multidisciplinary approach which is the approach of the fields of accounting and technology. Data collection methods in this study include documentation, observation, and interviews. Design interactive applications using Macromedia Flash Player 8. The results of the study provide an interactive application of accounting learning models called Accounters. This application consists of three main menus namely Material, Quiz, and Hangman (game). Therefore, the Accounters application makes it easy for students in vocational schools to better understand accounting, so they are able to make financial reports for companies when they work later. And able to increase student motivation in accounting.